ADVANCED OXIDATION PROCESSES, BIOREMEDIATION AND GLOBAL WATER SHORTAGE – A VISION FOR THE FUTURE - SUKANCHAN PALIT, (International Journal of Pharma and Bio Sciences, 2016)
The world of environmental engineering science and the future of advanced oxidation processes are moving steadily from one paradigm over another. Advanced oxidation processes are revolutionizing the future of industrial wastewater treatment. The vision of science, the brisk forays of technology and the future of mankind is moved from one visionary direction over another. Environmental challenges are gearing up for new dimensions of technological innovations. In such a critical juncture, AOP or advanced oxidation processes are ushering in a new future in the area of industrial wastewater treatment and global drinking water shortage. The author brings into the forefront of scientific scenario the immense potential of advanced oxidation processes, novel separation processes and the future perspectives of the application of non-conventional industrial wastewater treatment techniques. Environmental engineering is briskly surpassing one visionary frontier over another. The question of environmental sustainability and the wide concern of environmental restrictions have created an immense surge and instinctive striving towards newer tools such as advanced oxidation processes and bubble column reactors. Application of bubble column reactors has a newer definition in this present decade. A terminology title bio-ozonation evolved over the scientific horizon of human endeavour. Advanced oxidation processes are in today’s scientific endeavour surpassing visionary frontiers. Ozonation is no more a scientific illusion. Bioremediation along with ozonation will open up newer vision and a newer generation of scientific thought and scientific steadfastness. In the present treatise, the author delves deep into the present understanding and future dimensions of the science and engineering of advanced oxidation processes and particularly bio-ozonation. Bio-ozonation and bio- remediation have tremendous scientific potential and improved wastewater degradation efficiency. Wastewater reclamation and degradation of recalcitrant chemicals in industrial wastewater are the major targets of environmental engineering tools. In the present treatise, the author delineates with immense and cogent insight the effectivity and importance of environmental engineering techniques in details. The author skillfully touches upon the combination of ozonation and bioremediation with deep comprehension. History of science and technology has its own visionary path. Bioremediation will open up new windows of innovation in years and decades to come